Dreaming of autumn skies [large type] - Andrews, V. C. (Virginia C.) (Andrews, V. C. (Virginia C.). Sutherland series, 2025)
"With her mother deceased and her father remarried, Caroline is forced to live with her domineering grandfather. But having endured so much loss and cruelty in her young life, she is determined not to let her suffering be in vain. Soon, Caroline embarks on a campaign to reclaim her own power and win over the most influential person in her family. She will stop at nothing to build the life and the independence she so desperately dreams of."--